Analysis of Language Skills Competencies through the Intrinsic Elements of the Short Story with the Learning Motivation and Discovery Learning - Morelent, Yetty; Hidayat, Hendra; Herawati, Susi; ., Marsis; Karnilla, Riche (International Journal of Engineering and Technology, 2018)
The purpose of this study is to analyze language skills competencies using the intrinsic element of the short stories and its impact on studentsâ€™ learning motivation using discovery learning method in senior high school. The research was Quasi-Experiment with a 2x2 factorial design. Data collection was conducted through two instruments items; non-test (questionnaire) for the learning motivation and test (essay) for the ability to identify intrinsic elements of short stories. The results of the research indicated that firstly, the ability to identify intrinsic elements of short stories of the students who were taught by using discovery learning method is better than students ability who were taughtconventionally. Secondly, it means that the ability to identify the intrinsic elements of short stories of the highly motivated students who were taught by using discovery learning method was higher than highly motivated students who are taught by using conventional method.. Thirdly, the ability to identify intrinsic elements of theshort story of students who have low learning motivation taught by using discovery learning method is higher than the students have low learning motivation taught by using conventional methods. Finally, there is no interaction between discovery learning method and learning motivation on the ability to identify the intrinsic elements of the short stories.From the result, it can be concluded that discovery learning methods can be used in learning ability to identify the intrinsic element of short stories.Â